2007
DOI: 10.1002/jms.1250
|View full text |Cite
|
Sign up to set email alerts
|

Desorption electrospray ionization mass spectrometry of intact bacteria

Abstract: Desorption electrospray ionization (DESI) mass spectrometry (MS) was used to differentiate seven bacteria species on the basis of their measured DESI-mass spectral profile. Both gram-positive and gram-negative bacteria were tested and included Escherichia coli, Staphyloccocus aureus, Enterococcus sp., Bordetella bronchiseptica, Bacillus thuringiensis, Bacillus subtilis and Salmonella typhimurium. Distinct DESI-mass spectra, in the mass range of 50-500 u, were obtained from whole bacteria in either positive or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
63
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(63 citation statements)
references
References 44 publications
0
63
0
Order By: Relevance
“…Third, the last decade has seen very significant advances in MS with respect to ion sources and the sensitivity of the instruments themselves (20)(21)(22)(23)(24)(25)(26)(27). Ambient ionization methods combined with significant improvements in sensitivity and mass accuracy of MS instrumentation now enable the detection of intact molecules directly from surfaces (7,(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40). Using the ambient method nanoDESI, the molecular characterization of microbial colonies directly from agar surfaces without any prior sample preparation has become possible (7).…”
Section: Significancementioning
confidence: 99%
“…Third, the last decade has seen very significant advances in MS with respect to ion sources and the sensitivity of the instruments themselves (20)(21)(22)(23)(24)(25)(26)(27). Ambient ionization methods combined with significant improvements in sensitivity and mass accuracy of MS instrumentation now enable the detection of intact molecules directly from surfaces (7,(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40). Using the ambient method nanoDESI, the molecular characterization of microbial colonies directly from agar surfaces without any prior sample preparation has become possible (7).…”
Section: Significancementioning
confidence: 99%
“…For example, MS analysis and identification of microorganisms, mostly performed by commercial platforms based on MALDI, is revolutionizing the field of microbiology [30]. Similarly, using DESI, direct analysis of microorganisms showed that characteristic constituents of bacteria can be detected; in particular, acylium ions of FA are observable directly, not as the usual methyl ester derivatives [32,33]. DESI allows rapid in situ analysis of samples in their native state and has been used to study the chemical composition of animal tissues, plants, and documents in an untargeted fashion [34].…”
Section: Introductionmentioning
confidence: 99%
“…Although GC-MS instruments currently dominate the portable mass spectrometry industry, estimates indicate that the confidence for molecule identification by MS/MS is about that provided with GC-MS (when combining MS information with retention time) [15]. The MS/MS-capable CITbased instrument enables chromatography-free analysis for high confidence in situ molecule identification with 100-fold faster analysis times than standard GC-MS analyses.Atmospheric pressure desorption ionization techniques, including DESI and DART, are capable of generating ions of diverse chemical nature directly from solid surfaces for MS/MS analysis [10,[16][17][18][19][20][21][22][23][24][25][26][27][28][29][30]. In forensic [26,31], security [19,32], and quality control applications [17,27], desorption techniques provide actionable chemical information through rapid, definitive analyses.…”
mentioning
confidence: 99%